Trend in the utilization of antenatal care during pregnancy among the adolescents in Bangladesh: Evidence from national survey data 2012/2013 and 2019 - Md. Sabbir Ahmed (Wiley, 2021)
Abstract Introduction Pregnancy during adolescence is a global health problem and the leading cause of maternal mortality. This study was aimed to explore the trends of the utilization of prenatal care or antenatal care (ANC) services during 2012/2013 and 2019, and to identify the factors associated with the use of ANC among adolescents in Bangladesh. Methods This study was based on the secondary data set of two consecutive surveys of Bangladesh Multiple Indicator Cluster Survey (MICS) 2012/2013 and 2019. Results The prevalence of utilizing ANC among Bangladeshi adolescents is in increasing trend; however, as per WHO recommendation, the prevalence of utilizing 4+ ANC visits was very low in 2019 (34.1%), which was 26.2% in 2012/2013. Educational status of the adolescents, area of residence, household wealth status, administrative division, and status of watching television were independent predictors of receiving 4+ ANC visits among the pregnant adolescent girls in Bangladesh. Conclusions The status of ANC among Bangladeshi adolescents is still very low. Awareness building programs among adolescents and their family members through health education interventions should be taken.